Property rights for poverty reduction? - Meinzen-Dick, Ruth S. (United Nations Department of Economic and Social Affairs, 2009)
This paper reviews the links between property rights and poverty reduction. Poor people not only lack current income, but also assets with which to generate incomes. Billions of poor people have access to land which may not be legally recognized. While legislation may provide more secure land tenure for the poor and thus reduce poverty, this outcome is not guaranteed. Policies that do not recognize the complexity of property rights have backfired, reducing poor people's security of tenure. Finally, understanding legal pluralism can lead to more effective policies and interventions to strengthen poor people's control over assets.